Meaningful Transfer: Tech-Knowlogical Interdependencies in the Digital Built Environment - Muldoon-Smith, Kevin; Moreton, Leo; Kotter, Richard (Frontiers in Sustainable Cities, 2021)
This paper engages with ideas of tacit and explicit knowledge, how it is created, transferred, and ultimately translated in contemporary discourses of the digital built environment. The aim is to open a more critical and original dialogue in the digital built environment by (a) interrogating digital innovation as it strives to utilise relatively distilled information to enhance the sustainable design, construction and operation of the built environment and wider urban areas, (b) representing the rights of those whose knowledge is created and transferred in the digital built environment and (c) by further understanding the context of knowledge creation, and thus maximising its potential for scaling up sustainability objectives. The paper considers the conceptual and methodological tools that may help to focus more novel analysis of knowledge production and transfer in the digital built environment. The paper considers three conceptual positions that have hitherto been considered either in isolation or only tangentially connected to each other: (1) Science and Technology Studies (STS), in order to understand how society and technology is intertwined and importantly to form a meaningful backdrop for engagement with knowledge; (2) Organisational Theory (OT) and the concept of “pipelines,” in order to understand how organisations—and more broadly cities—can meaningfully capture and utilise knowledge when transitioning to digitally enabled sustainable futures; (3) Aspects of Actor Network Theory (ANT), in order to understand how knowledge travels and gets translated and institutionalised in new domains. Furthermore, we also use the same conceptual positions to argue how following knowledge can help individuals and society navigate the digital built environment. Our findings suggest that smart technology is a “social prosthesis,” and only works because humans make up for its deficiencies.